Haematological responses of nile tilapia (Oreochromis niloticus Linnaeus 1758) to exposure to effluent from palm oil mills - Muliari, Muliari; Akmal, Yusrizal; Irfannur, Irfannur; Zulfahmi, Alim; Istiqomah, Indah; Ulfa, Maria; Batubara, Agung S. (Charles University in Prague, 2022)
Pollution by palm oil mill effluent (POME) is of great concern in Indonesia. POME pollution of the water can adversely affect aquatic organisms, especially fish. This study aims to analyse the effect of POME on the haematology of tilapia (Oreochromis niloticus), including red blood cells (RBC), white blood cells (WBC), haemoglobin (Hb), Mean Corpuscular Haemoglobin Concentration (MCHC), Mean Corpuscular Haemoglobin (MCH), Mean Corpuscular Volume (MCV) and haematocrit. A random experimental design was used (CRD) consisting of four treatments and five replications, including a Control (0% POME): Treatment A (10% of LC50-96 hours: 1.565 mg l-1), Treatment B (15% of LC50-96 hours: 2.347 mg l-1) and Treatment C (20% of LC50-96 hours: 3,130 mg l-1). The analysis of blood of fish exposed to POME for 15, 30 and 45 days revealed significant effects (p < 0.05) only on Hb and MCH on day 15 and WBC on day 30. This study indicates that exposure to POME can reduce the WBC value of tilapia recorded on day 30 in treatment C to a level lower than that recorded in other treatments. The Hb value recorded for tilapia exposed to POME on day 15 in treatment C was significantly higher than in the other treatments. Furthermore, POME caused a significant decrease in MCH recorded on day 15, with the lowest value recorded in treatment A. Based on the results of this study, POME can cause a significant decrease in WBC recorded on day 30 and MCH on day 15 and increase in Hb on day 15 in tilapia.